Conception and realization of a PV system provided with a sun tracker operating at dual axis - Khalil Kassmi; Rajae Gaamouche; Ali Lamkaddem; Soufian Talbi (Renewable Energy and Sustainable Development, 2016)
In this paper, we present the conception, the realization and the experimentation of  a photovoltaic (PV) system provided with a sun tracker reliable and low cost operating at dual axis. The tracker's role is to orient the PV generator, whose weight may reach 9 Kg, perpendicular to the sun with very good accuracy. This tracking  based on the use of four LDR sensors, which detect the intensity of light scattered by the sun a processing unit, from  command and control (UTCC), which manages all of the sun tracking tasks (the end detection of parcours, regulation of the power supplied by the PV panels (Command MPPT), ... ). The results obtained show a significant improvement of the energy produced, compared to conventional PV installations where generators are fixed and oriented south at a  tilt 45°. During a day of operation, improvement could reach 41% and consumption of the tracking does not exceed 0.55% of the energy production produced by the PV generator (an improvement of 5 % compared to existing trackers).